The State of Neutrophilic Granulocyte Indices in Patients with Acute Infected Necrotizing Pancreatitis Depending on the Type of Pathogen - Stasenko, А.A.; Dibrova, Yu.A.; Стасенко, А.А.; Діброва, Ю.А. (PH "Akademperiodyka" of the NAS of Ukraine, 2026)
The aim of the work was to study the state of polymorphonuclear leukocytes (PMN) in patients with acute infected necrotizing pancreatitis (AINP) depending on the type of pathogen. Methods. In patients with AINP in the preoperative period and in patients of the control group, the metabolic activity of blood neutrophils in the SP and ST test with nitroblue tetrazolium (NBT), as well as the PR of metabolic activity were determined in the blood. The percentage of active PMN in the phagocytosis reaction (a percentage of neutrophils involved in phagocytosis) and the number of absorbed Candida albicans particles on average by one PMN - PhI were studied. Results. Pseudomonas aeruginosa, Escherichia coli, Enterococcus faecalis, Klebsiella pneumoniae, Acinetobacter baumannii, and Staphylococcus epidermidis were the most common bacterial pathogens identified in AINP patients. The patients with G(-) microorganisms had a significantly increased number of formazan-positive blood PMN in the ST NBT test, as well as PhN of blood PMN  compared to patients with G(+) microorganisms. The metabolic activity and phagocytic index of blood PMN  in patients with infected APN did not differ depending on the monoculture or association with isolated microorganisms. However, patients with a monoculture of microorganisms had a significantly increased PMN blood phagocytic index compared to patients with microbial associations. Conclusions. In patients with acute necrotizing pancreatitis, there are disturbances in the functional activity of the PMN. The main directions of the disorders are a significant activation of the processes of blood PMN metabolism. A significantly increased PhN of blood PMN was found in patients with G(-) microorganisms compared to patients with G(+) microorganisms. It was found that patients with microorganisms monoculture had a significantly increased PhN of blood PMN compared to patients with microbial associations.